Ottoman Turkey the Sorrowful Period of Islam's Political Journey - Puja Khaerunnisa; Marsha Elvyadi Elvyadi Rahma; Imam Tabroni; Xie Guilin; Yuanyuan Wang (Yayasan Adra Karima Hubbi, 2023)
Background. Talking about Islam cannot be separated from the long history of the struggle of Muslims in the world. Purpose. History is strong evidence that a civilization can be seen to exist and the fragrance of its name. Method. According to the literature, history is an event or event that really happened in the past, science, knowledge, lesson stories about events or events that have really happened. Results. Since Islam was born until now, there have been many dynamics of civilization that can be learned as lessons and encouragement for the people afterwards. Conclusion. From this history, Muslims are increasingly aware that their predecessors left a scientific and civilizational legacy that can be emulated for the people after them in the future